2020
DOI: 10.1093/brain/awaa360
|View full text |Cite
|
Sign up to set email alerts
|

Acute and non-resolving inflammation associate with oxidative injury after human spinal cord injury

Abstract: Traumatic spinal cord injury is a devastating insult followed by progressive cord atrophy and neurodegeneration. Dysregulated or non-resolving inflammatory processes can disturb neuronal homeostasis and drive neurodegeneration. Here, we provide an in-depth characterization of innate and adaptive inflammatory responses as well as oxidative tissue injury in human traumatic spinal cord injury lesions compared to non-traumatic control cords. In the lesion core, microglia were rapidly lost while intermediate (co-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 72 publications
5
110
0
Order By: Relevance
“…As a marker of A1 astrocytes, the expression of C3 began to be signi cantly upregulated at 7 dpi and strengthened in the following 28 dpi. Therefore, we conclude that neurotoxic microglia and astrocytes are activated in succession in the acute and subacute phases of SCI, and both of them are involved in secondary neuroin ammation, which is consistent with previous reports [33,34]. In view of the fact that little is known about the activation of M1 and A1, we tried to identify the underlying mechanism through RNAseq analysis.…”
Section: Discussionsupporting
confidence: 89%
“…As a marker of A1 astrocytes, the expression of C3 began to be signi cantly upregulated at 7 dpi and strengthened in the following 28 dpi. Therefore, we conclude that neurotoxic microglia and astrocytes are activated in succession in the acute and subacute phases of SCI, and both of them are involved in secondary neuroin ammation, which is consistent with previous reports [33,34]. In view of the fact that little is known about the activation of M1 and A1, we tried to identify the underlying mechanism through RNAseq analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Despite being known as a homeostatic marker [ 45 ], several studies have shown a stable expression of TMEM119 also in response to injury and inflammatory conditions. In spinal cord injuries, TMEM119-positive cells also stained positive for typical activation markers, such as MHCII and CD68, detecting a pro-inflammatory activation of microglial cells [ 46 ]. However, necrotic lesions of cerebral infarctions and demyelinating lesions of multiple sclerosis were devoid of TMEM119 expression [ 45 ].…”
Section: Tmem119mentioning
confidence: 99%
“…Due to the decrease in its expression in an activated microglial status, P2RY12 is usually described as a homeostatic marker [ 53 , 59 ]. However, Zravy et al [ 46 ], detected a return of low numbers of P2RY12-positive cells in the late stages of the injury process in human spinal cord injury.…”
Section: P2ry12mentioning
confidence: 99%
“…Visualization was performed by using (1) alkaline phosphatase-conjugated secondary antibodies for subsequent development with fast blue BB salt as well as (2) biotinylated secondary antibodies and peroxidase-conjugated streptavidin for subsequent development with aminoethyl carbazole (AEC). 17,18 NMDAR Antibody Testing CSF NMDAR antibodies were assessed using an in-house tissue-based assay as described elsewhere 1 and a commercial cell-based assay (Euroimmun, Lübeck, Germany) according to the manufacturer's protocol. Positivity was defined as a positive neuropil staining pattern in the tissue-based assay and positive labeling of transfected cells.…”
Section: Neuropathology and Immunohistochemistrymentioning
confidence: 99%